The Heritage of Traditional Superior Beers from the Visegrad Group Countries - Fiala, Jaromír; Šmogrovičová, Daniela; Kun-Farkas, Gabriella; Kordialik-Bogacka, Edyta; Vinopal, Jiří (KVASNY PRUMYSL, 2017)
Preferences in the consumption of food and drinks can change according to eating habits. A consumer test with total 320 participants held in the countries of the Visegrad Group (Visegrad Four) in April 2016 confi rmed, however the popularity of regional beers, particularly those with a medium original wort extract (about 11.5 to 12.0 % wt), with medium to high bitterness, high body-fullness, high carbonation and medium alcohol content. Some groups of participants had different preferences but the beers with lower bitterness, lower original wort extract and lower sharpness were generally rated lower.